Ethnomedicine Study on the Use of Medicinal Plants in Batak Ethnic Communities: Kajian Etnomedisin Pemanfaatan Tumbuhan Obat Pada Masyarakat Etnis Batak - Rahmadani, Dessi; Harianti, Chita; Hasanah, Nurul; Arsya, Dinara Eza Syahadati; Zahrah, Nabila; Puspitawati, Ni Komang Anika; Sari, Karin Sopiya; Joshevine, Imelda; Filicia, Harfenas Althea; Asia, Nazha Delmora; Brigita, Vista; Ahmad, Islamudin (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
Ethnomedicine is the study of ethnobotany to reveal the knowledge and local wisdom of various ethnicities in order to maintain and maintain health. The Batak tribe is the largest tribe inhabiting the island of North Sumatra where the Batak ethnic community has a traditional medicine culture inherited by their ancestors from generation to generation in the form of a medical book with Batak script writing. The purpose of this paper is to convey the type or species of plants used in some disease treatments in Batak tribal communities and find out whether the type or species of plants used has data that supports its use as a treatment for a disease based on literature searches. The method used is systematic literature review. A comprehensive literature search was conducted using several databases such as Google Scholar, PubMeb, ScienceDirect, ResearchGate. Based on a study of known references, medicinal plants that are often used by the Batak tribe are plants from the Asteraceae, Fabaceae, Zingiberaceae, and Poaceae families to treat various diseases. A typical plant from the Batak tribe is the Pirdot plant (Saurauia bracteosa) which is usually used to reduce high blood pressure.